Verifying Determinism in Sequential Programs - Mudduluru, Rashmi; Waataja, Jason; Millstein, Suzanne; Ernst, Michael (2021 IEEE/ACM 43rd International Conference on Software Engineering: Companion Proceedings (ICSE-Companion), 2021)
When a program is nondeterministic, it is difficult to test and debug. Nondeterminism occurs even in sequential programs iterating over the elements of a hash table. We have created a type system that expresses determinism specifications in a program. The key ideas in the type system are type qualifiers for nondeterminism, order-nondeterminism, and determinism; type well-formedness rules to restrict collection types; and enhancements to polymorphism that improve precision when analyzing collection operations. We implemented our type system for Java. Our type checker, the Determinism Checker, warns if a program is nondeterministic or verifies that the program is deterministic. In this paper, we explain how to obtain our tool and reproduce the results described inhttps://homes.cs.washington.edu/ mernst/pubs/determinismicse2021.pdf. Additionally, our tool and subject programs are available at https://zenodo.org/record/4536285#.YEaCxZNKiWw.